Implementation and evaluation of a pain management core competency education program for surgical nurses - Xuelian Liu; Li Li; Lingxiao Wang; Keela Herr; Qiuchan Chen (Elsevier, 2021)
Objective: To investigate the effect of a pain management core competency education program on surgical nurses' pain knowledge and pain management nursing practice behaviors. Methods: An 8-h education program focused on pain management core competency was provided twice in two weeks including the multidimensional nature of pain, pain assessment, pharmacological and non-pharmacological management, and knowledge application was developed and implemented for surgical nurses by a multidisciplinary team. Multimodal teaching approaches such as didactic teaching and vignettes of cases for nurses to discuss were used. The Clinical Pain Knowledge Test (CPKT) was completed by 135 and 107 nurses from 17 surgical wards pre and post-program, respectively. Two hundred and three patients' medical records were randomly sampled according to the number of operations in each ward one week before and in the fifth week after the intervention, respectively. Documentation of patients' postoperative pain management nursing practice behaviors and pain intensity scores were collected. Results: After the intervention, the CPKT scores of nurses significantly increased from 45.6% ± 12.3% to 54.2% ± 10.2% (t = 5.786, P < 0.001). Nurses' postoperative pain management nursing practice improved, with proportion of pain assessment documentation increased from 59.6% (121/203) to 74.9% (152/203) (χ2 = 10.746, P = 0.001), those using pain intensity assessment tools increased from 81.8% (99/121) to 95.4% (145/152) (χ2 = 13.079, P < 0.001), and intramuscular injection of nonopioids decreased from 12.6% (13/103) to 2.7% (3/111) (χ2 = 7.598, P = 0.006). Patients' average worst pain score on the operation day significantly decreased (Z = −2.486, P = 0.013), and scores from the first to the third postoperative day also decreased (Z = −2.172, P = 0.030). Conclusions: Implementation of a pain management core competency education program for surgical nurses can increase their knowledge of core competencies of pain management, improve selected pain management practices, and decrease patients' postoperative pain intensity.